GAMBARAN INTELIGENSI ANAK PRA SEKOLAH YANG DIASUH DI PANTI ASUHAN - Maria Dwi Yanika Hesti Nugraha (Psibernetika, 2011)
Childhood is the the beginning period of the development of intelligence, the role of adult and parenting environment can initially be applied to develop the cognitive abilities of children. Subjects in this study were pre-school children who are raised in an orphanage, with the best upbringing. This study is a descriptive quantitative research, data collection techniques using survey techniques and analyzed by descriptive data analysis techniques. These results indicate that the intelligence picture of preschool children who are raised in foster homes in the category of above average percentage of 75% of the sample, intelligence is measured using a CPM test (Coloured Progressive Matrics).Keywords : intelligence, anak pra sekolah, orphanage